Growth Enhancement for Increasing Papaya Production with Mycorrhizal and Manure Applications in Dry Land Conditions: Daya Dukung Pertumbuhan terhadap Peningkatan Produksi Pepaya dengan Aplikasi Mikoriza dan Pupuk Kandang di Lahan Kering - Anditya Gilang Rizky Pradana; Cahyaningtyas Putri Suhita; Desy Setyaningrum; Dewi Nawang Suprihatin; Didik Suryadi; Dimar Hantari; Edi Paryanto; Febry Nurhidayati; Hardian Ningsih; Zainal Arifin (Universitas Widya Gama Mahakam, 2025)
Papaya is a horticultural commodity with many benefits and high economic value for the people of Indonesia. California papaya is a favorite variety in Indonesia due to its various advantages. Effective and agroecological cultivation techniques are needed to increase production. This study aims to determine the optimal dosage of mycorrhizae and manure in increasing papaya plant growth. This study was conducted in the dry land of Tawengan Village, Sambi District, Boyolali Regency, at 180 m above sea level. The research used a factorial Complete Randomized Block Design (CRBD) with 3 blocks as replications. The first factor was mycorrhizae with 3 levels: 0 g/plant, 75 g/plant, and 150 g/plant. The second factor was manure with 4 levels of application doses: 0 kg/plant, 3 kg/plant, 6 kg/plant, and 10 kg/plant. The results showed that the application of mycorrhizae and manure can improve the characteristics of plant height, stem diameter, and crown width. The mycorrhizal application dose of 150 g/plant and the application of 5.7 kg/plant of manure is the optimal dose to increase papaya growth, which will support increased production.